IMPLEMENTASI PERLINDUNGAN HUKUM TERHADAP KORBAN KDRT BERDASARKAN UU NO. 23 TAHUN 2004 DI LUBUKLINGGAU - Fitriyani, Aidil; Fuadi, Ahmad; Fitriyani, Fitriyani (LPPM Universitas Bina Insan, 2025)
Domestic violence (KDRT) is a violation of human rights and a form of crime against humanity that often occurs in the private space of the household. Law Number 23 of 2004 concerning the Elimination of Domestic Violence is present as a form of legal protection to prevent, take action, and recover victims of domestic violence. This study aims to analyze the implementation of the law in Lubuklinggau City, identify the obstacles faced by law enforcement officials, and describe the legal and social consequences caused. The normative-empirical approach was used through a study of laws and regulations and interviews with the Lubuklinggau City Women's Empowerment and Child Protection Office. The results of the study show that although regulations have regulated strict criminal sanctions against perpetrators, their implementation still faces obstacles, such as patriarchal culture, lack of public understanding, and limited protection and recovery of victims. Domestic violence has a wide impact, both physically, psychologically, socially, and economically, and can even trigger divorce and household rifts. Therefore, law enforcement must be accompanied by public education and increasing the role of victim service institutions. Keywords: Legal Protection, Domestic Violence .